PENINGKATAN KETERAMPILAN MENULIS KALIMAT SEDERHANA SISWA KELAS I MELALUI MEDIA PEMBELAJARAN STORYBOARD - Saputri, Mey Linda Eka; Rofiq, Muhammad Aunur; Kurniawan, Wildan Farih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students in lower elementary grades still experience difficulties in writing simple sentences because learning activities tend to rely on conventional methods and less engaging media. This condition was also found in grade I students at SDN 2 Nglengkir, where many students struggled to arrange sentences coherently and independently. This study aimed to improve students’ simple sentence writing skills through storyboard learning media. PBL is used in research. The research used Classroom Action Research based on the Kemmis and Taggart model conducted in two cycles involving 9 first-grade students. Data were collected through observation, interviews, and documentation. The assessment focused on sentence structure, content suitability, language use, and idea coherence. The results showed a gradual improvement in students’ writing skills in each cycle. Learning mastery in the pre-cycle was 44,44% with an average score of 70.9. After the implementation of storyboard media in cycle I, mastery increased to 77,78% with an average score of 74.1. In cycle II, learning mastery reached 100% with an average score of 80.45. Storyboard media helped students connect visual sequences into written ideas more easily and systematically. The study indicates that storyboard media can support more concrete and meaningful writing instruction for lower-grade elementary students.